2013
DOI: 10.1159/000346319
|View full text |Cite
|
Sign up to set email alerts
|

Female Gender and Reproductive Factors Affecting Risk, Relapses and Progression in Multiple Sclerosis

Abstract: Multiple sclerosis (MS), a chronic inflammatory demyelina-ting and degenerative disease of the central nervous system, is a frequent cause of neurological disability in young adults. Female predominance has increased over the last decades. Although female gender carries a higher risk of developing relapsing remitting MS, being female and at child-bearing age also appears to provide some protection against cognitive decline and against progressive onset MS, an adverse predictive factor when considering long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 108 publications
1
23
0
6
Order By: Relevance
“…Fertility treatments utilizing gonadotropin releasing hormone (GnRH) agonists may also increase the risk of relapse in MS patients, especially when it does not result in pregnancy 90 Lastly, the presence of two X chromosomes was shown to increase susceptibility to MS in animal models independent of hormone levels. 91 …”
Section: Non-infectous Uveitidesmentioning
confidence: 99%
“…Fertility treatments utilizing gonadotropin releasing hormone (GnRH) agonists may also increase the risk of relapse in MS patients, especially when it does not result in pregnancy 90 Lastly, the presence of two X chromosomes was shown to increase susceptibility to MS in animal models independent of hormone levels. 91 …”
Section: Non-infectous Uveitidesmentioning
confidence: 99%
“…Pregnancy is a state of relative maternal immune suppression to accommodate the semi-allogeneic fetus [5,6,7]. The clinical features of CCHF infection are well known.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to former belief, current studies revealed that pregnancy has no negative effect on MS [18]. Although limited data had existed and results were conflicting, no association between parity and conversion to SPMS has been shown [1,19,20,21,22,23]. …”
Section: Discussionmentioning
confidence: 89%